A rare unbalanced translocation (trisomy 5q33.3‐qter, monosomy 13q34‐qter) results in growth hormone deficiency and brain anomalies. Issue 11 (8th October 2021) - Joynt, Alyssa C. M.; Deshwar, Ashish R.; Zon, Jessica; Dupuis, Lucie; Wherrett, Diane K.; Mendoza‐Londono, Roberto
Abstract: Background: Unbalanced translocations between the q arm of chromosomes 5 and 13 are exceedingly rare and there is only one reported case with distal trisomy 5q/monosomy 13q. In this report, we describe a second patient with a similar rearrangement arising from a paternal balanced translocation. Methods: Karyotype analysis was performed on the proband and their parents. Microarray was also conducted on the proband. Results: Our patient was found to have global developmental delay, distinct facial features, short stature, growth hormone deficiency, delayed puberty, and brain anomalies including a small pituitary. Karyotype and microarray analysis revealed a terminal duplication of chromosome regions 5q33.3 to 5qter and a terminal deletion of chromosome regions 13q34 to 13qter that resulted from a balanced translocation in her father. The endocrine abnormalities and neuroimaging findings have not been previously described in patients with either copy number change. Conclusions: This case helps expand on the phenotype of patients with distal trisomy 5q/monosomy 13q as well as possibly providing useful information on the more common individual copy number changes. Abstract : In this report, we describe a patient with a terminal duplication of chromosome regions 5q33.3 to 5qter and a terminal deletion of chromosome regions 13q34 to 13qter. Only one patient has been so far reported with a similar genetic complement, and in our patient, we report unique features including growth hormone deficiency and brain anomalies. We review the clinical features previously described in patients with distal trisomy 5q and monosomy 13q and find that neither of these has been reported in patients with either copy number variation.